Von einer „Imperatorix“ zu einer „mulier clara“. Kaiserin Konstanze im Spiegel von „Liber ad honorem Augusti sive de rebus siculis“ und „De claris mulieribus“ - Paul Andreas Csillag (Historia.scribere)
The following paper discusses the image of the Staufer empress Konstanze. This important political person was described in two books. On the one hand, Peter of Eboli draws her as a female heroine; on the other hand, the famous writer Giovanni Boccaccio projected his misogyny on her. Their depictions of Konstanze differ enormously due to various ideological mindsets. This text shows how a person herself can become a political term.